The Bishops of the Diocese of Vilnius and Lithuanian Domestic Politics in 1709–17: Attitudes, Problems, and Solutions - Šapoka, Mindaugas (Acta Poloniae Historica, 2022)
The article looks into the participation of the bishop ordinary of the diocese of Vilnius, Kazimierz Konstanty Brzostowski, and his suffragan, Maciej Józef Ancuta, in Lithuanian politics of the period between 1709 and 1717. The study has been based on the letters written by the bishops to the Lithuanian chancellor. It examines the bishops’ attitude towards Russian contributions, the taxation of Church estates, the arbitrary contributions raised by the Lithuanian army, the introduction of Saxon troops in 1713, the reaction to the king’s policies, and the attitude towards the nationwide uprising against the Saxon troops known as the confederations of Tarnogród and Vilnius. Finally, the bishops’ opinion on Russian mediation and the notorious Silent Sejm, where it was agreed that the liberum veto would be invalid. The bishops of the diocese of Vilnius were rather indifferent to the internal problems of Lithuania. They defended the immunity of the Church estates and disapproved of the introduction of Saxon troops. However, when the confederations were formed, they tried to manoeuvre between the noble and royal camps, not wanting to ruin their reputation on either side. The bishops often spoke on behalf of the diocesan clergy. Therefore, their adopted posture was often the expression of the opinion of the whole diocese’s clergy.